A organização do conhecimento e a representação do conhecimento no domínio da arquivística - Silva, Irisneide de Oliveira Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This study focuses on the theme of the organization and representation of knowledge in the field of Archival Science, presenting a challenge that is central to the discussion of theoretical and methodological foundations that involve the process of arrangement and archival description in the universe of archives. Although arrangement and archival description are recurrently treated in the systematized literature in this area, the vast majority of studies tend to emphasize the technical side, while theory is pushed to the background. This issue shows the need of a theoretical deep study on the organization and representation of knowledge in this domain. This research supports the hypothesis that the theoretical and methodological studies in the area of Organization and Representation of Knowledge are essential for deepening Archival Science. It supports the thesis that the need to understand organization and representation of knowledge in Archival Science converges to the theoretical and methodological reflection on arrangement and archival description in the very corpus of Archival Science. Therefore, the research proposes to investigate the grounds on which the organization and representation of knowledge are in the field of the present Archival Science, focusing its processes of arrangement and archival description. Thus, it hopes to contribute to the debate on the issue of organization and representation of knowledge in the area of Archivists as an Information Science area. Specific research objectives are: 1. To discuss the theoretical foundations of Archival Science and the process of documental treatment; 2. To investigate the contributions of Organization of Knowledge within the scope of ISKO based on the Classification Scheme for Knowledge Organization Literature (CSKOL) of Dahlberg for the organization ... (Complete abstract click electronic access below)

Este estudo focaliza a temática da organização e da representação do conhecimento no domínio da Arquivística, apresentando como desafio central a discussão dos fundamentos teóricos e metodológicos que envolvem o processo de classificação e de descrição no universo dos arquivos. Embora a classificação e a descrição sejam tratadas de forma recorrente na literatura sistematizada na área, a grande maioria dos estudos tende a valorizar a face técnica, enquanto a teórica é postergada para o segundo plano. Esse problema traz no seu bojo a necessidade do aprofundamento teórico acerca da temática da organização e da representação do conhecimento nesse domínio. Nesta investigação defende-se a hipótese de que os estudos teóricos e metodológicos da área de Organização e Representação do Conhecimento são essenciais para o aprofundamento da Arquivística. Defende-se a tese de que a necessidade de se compreender a organização e a representação do conhecimento no domínio da Arquivística converge para a reflexão teórica e metodológica da classificação e descrição no próprio corpus da Arquivística. Assim, a pesquisa propõe-se a investigar os fundamentos nos quais se circunscrevem a organização e a representação do conhecimento no domínio da Arquivística atual, com enfoque em seus processos de classificação e descrição. Desta forma, espera-se, contribuir com o debate acerca da problemática da organização e representação do conhecimento no domínio da Arquivística enquanto área da Ciência da Informação. São objetivos específicos da pesquisa: 1. Discutir os fundamentos teóricos da Arquivística e seu processo de tratamento documental; 2. Investigar os contributos da Organização do Conhecimento...
Keywords: Arquivologia; Teoria do conhecimento; Representação do conhecimento (Teoria da informação); Ciência da informação